Learning loss during the pandemic: Views of Indonesian teachers and parents - Costrie Ganes Widayanti; Prasetyo Budi Widodo; Yeniar Indriana; Ika Febrian Kristiana (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The pandemic situation has dramatically caused a shift from face-to-face learning to online-based distance learning. Learning loss has become an unanticipated impact and threatens almost all students in the world, including Indonesia. This qualitative study was aimed to explore the understanding of teachers and parents in Indonesia about learning loss. A total of 16 participants consisting of teachers and parents (M.age = 44.5; Female = 81.25%; Male = 18.75%) were involved in focus group discussions as the data collection process. This is narative research using thematic analysis from Braun Clarke (2006) was used in data analysis. There were 6 final themes about learning loss, namely: the determinants, the forms, the negative impacts, the strategies to minimize, the parties who are responsible for overcoming it, and the expectations of teachers and parents. The unique findings of this study establishing the possibilities for future research include decreased motivation and positive characters as a new form of learning loss, teacher capacity in conducting online learning, technological literacy for parents, and learning loss for students with special needs as well as network constraints and unnecessary involvement from parents (finishing student assignments) as parts of the causes of learning loss. It is necessary to have a strategy in overcoming learning loss in a collaborative effort from various parties responsible for the education system in Indonesia.